Analisis Kesiapsiagaan Masyarakat dalam Menghadapi Bencana Banjir di Nagari Talang Babungo - Risma Dani; Triyatno Triyatno (JURUSAN GEOGRAFI FIS UNP, 2022)
This study aims to: 1). To find out the preparedness of the people of Nagari Talang Babungo in dealing with floods in terms of disaster knowledge. 2). To find out the preparedness of household policies in Nagari Talang Babungo. 3). To know the preparedness of disaster emergency response in Nagari Talng Babungo. 4). To find out the preparedness of disaster early warning in Nagari Talang Babungo. 5). To find out the preparedness of community resources in dealing with disasters in Nagari Talang Babungo This type of research uses descriptive quantitative methods. The technique of collecting data by conducting interviews, questionnaires and documentation. Sources of data from this study using primary data obtained and collected by researchers directly in the field and using secondary data obtained from journals and related agencies. The results of this study: 1). The knowledge preparedness of the people of Nagari Talang Babungo is in the high category with an average of 67%. 2). The preparedness of community policies in dealing with disasters in Nagari Talang Babungo is in the less prepared category with an average disaster hazard index of 54%. 3). Emergency response preparedness in dealing with disasters in Nagari Talang Babungo is categorized as not yet ready with an average disaster hazard index of 19%. 4). Disaster early warning preparedness in Nagari Talang Babugo is in the almost ready category with a disaster hazard index of 56%. 5). The preparedness of community resources in dealing with disasters is classified as not ready with an average of 15%. 6). The community preparedness index in dealing with flood disasters in Nagari Talang Babungo is classified as less prepared.